Assessment of inattention in the context of delirium screening: one size does not fit all!. (23rd March 2016) - Voyer, Philippe; Champoux, Nathalie; Desrosiers, Johanne; Landreville, Philippe; Monette, Johanne; Savoie, Maryse; Carmichael, Pierre-Hugues; Richard, Sylvie; Bédard, Annick
ABSTRACT: Background: Despite its high prevalence and deleterious consequences, delirium often goes undetected in older hospitalized patients and long-term care (LTC) residents. Inattention is a core symptom of this syndrome. The aim of this study was to explore the usefulness of ten simple and objective attention tests that would enable efficient delirium screening among this population. Methods: This was a secondary analysis ( n = 191) of a validation study conducted in one acute care hospital (ACH) and one LTC facility among older adults with, or without, cognitive impairment. The attention test tasks ( n = 10) were drawn from the Concentration subscale the Hierarchic Dementia Scale (HDS). Delirium was defined as meeting the criteria for DSM-5 delirium. The Confusion Assessment Method (CAM) was used to determine the presence of delirium symptoms. Results: The Months of the Year Backward (MOTYB) test, which 57% of participants completed successfully, showed the best balance between sensitivity and specificity (82.6%; 95% CI [61.2–95.0], and 62.5%; 95% CI [54.7–69.8] respectively) for the entire group. Subgroup analyses revealed that no test had both sensitivity and specificity over 50% in participants with cognitive impairment indicated in their medical chart. Conclusions: Our results revealed that these tests varied greatly in performance and none can be earmarked to become a single-item screening tool for delirium among older patients and residents with, or without, cognitive impairment. The presence of premorbid cognitive impairment may necessitate more extensive assessments of delirium, especially when a change in general status or mental state is observed.